2011
DOI: 10.2527/jas.2010-3369
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous and intramuscular adipose tissue stearoyl-coenzyme A desaturase gene expression and fatty acid composition in calf- and yearling-fed Angus steers1

Abstract: We proposed that stearoyl-CoA desaturase (SCD) activity dictates fatty acid composition of adipose tissue and muscle in beef cattle, regardless of ruminal or hepatic fatty acid hydrogenation or desaturation. Twelve Angus steers were assigned to a calf-fed (CF) group and slaughtered at weaning (8 mo of age; n=4), 12 mo of age (n=4), or 16 mo of age (n=4). Twelve steers were assigned to a yearling-fed (YF) group and slaughtered at 12 mo of age (n=4), 16 mo of age (n=4), and 17.5 mo of age (n=4; 525 kg, market we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 37 publications
(54 reference statements)
3
29
1
1
Order By: Relevance
“…The primals used for the current study were obtained at random from a commercial abattoir, and graded USDA Select. We have demonstrated that the MUFA:SFA ratio increases with USDA Quality Grade (Brooks et al, 2011;Chung et al, 2006), and the low MUFA:SFA ratios observed in the current study in part can be explained by the lesser quality grades of these beef carcasses. However, the unusually low MUFA:SFA ratios also suggest that these cattle spent a limited amount of time on a grain-based diet; pasture feeding of cattle strongly depresses SCD activity and the concentration of MUFA in beef cattle (Brooks et al, 2011;Chung et al, 2006Chung et al, , 2007Duckett, Pratt, & Pravan, 2009;Gilmore et al, 2011;Leheska et al, 2008).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The primals used for the current study were obtained at random from a commercial abattoir, and graded USDA Select. We have demonstrated that the MUFA:SFA ratio increases with USDA Quality Grade (Brooks et al, 2011;Chung et al, 2006), and the low MUFA:SFA ratios observed in the current study in part can be explained by the lesser quality grades of these beef carcasses. However, the unusually low MUFA:SFA ratios also suggest that these cattle spent a limited amount of time on a grain-based diet; pasture feeding of cattle strongly depresses SCD activity and the concentration of MUFA in beef cattle (Brooks et al, 2011;Chung et al, 2006Chung et al, , 2007Duckett, Pratt, & Pravan, 2009;Gilmore et al, 2011;Leheska et al, 2008).…”
Section: Discussioncontrasting
confidence: 45%
“…SCD is responsible for the synthesis of MUFA from SFA in animal tissues and its activity is highly sensitive to dietary manipulation and animal age. In beef cattle fed grain-based diets, the concentration of MUFA (and especially oleic acid) increases with time on feed Gilmore et al, 2011;Huerta-Leidenz et al, 1996;Smith et al, 2012), as SCD activity and gene expression increases with time fed a high-grain diet (Brooks, Choi, Lunt, Kawachi, & Smith, 2011;Chung, Yano, Kawachi, Smith, & Lunt, 2007). Slip point values differ between adipose tissue depot depending on the size and extent of differentiation of adipocytes (i.e., larger adipocytes have higher concentrations of MUFA) (Smith et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Especially, intramuscular fat (marbling) plays important roles in eating quality and composition of meat compared to other fats [1], [2]. Some literatures reported that intramuscular fat is different from other fats in three respects: adipocyte size, metabolic activities, and developmental timing [29][31].…”
Section: Discussionmentioning
confidence: 99%
“…It is restricted to certain areas in the body such as subcutaneous layer between muscle and dermis, around internal organs and between muscles. The amount and distribution of fat are important factors that influence the meat quality in the beef industry [1], [2]. For several decades, it has been known that adipose tissues are regionally heterogeneous with respect to metabolic activities and functions [3][5].…”
Section: Introductionmentioning
confidence: 99%
“…Microscopically, marbling fat appears in specific adipose depots wherein adipocytes are embedded in a connective tissue matrix close to a blood capillary (Albrecht et al 2006). Intramuscular adipose tissue has direct impact on improving the quality of beef products and is the basis of quality grading (Lengi & Corl 2010;Brooks et al 2011;Dodson et al 2010). With the aim to produce livestock with better quality meat for consumers, intramuscular fat content has been at the centre of high quality beef production because it positively affects the sensory quality traits such as taste and flavour.…”
Section: Introductionmentioning
confidence: 99%